Cultural codes: essence, structure and functioning in the process of communication - V. M. Savitsky (Дискурс профессиональной коммуникации, 2019)
The article contains a critical review of the interpretations of the concept cultural code and proposes the author’s own definition. The author points out versatility of the notion in question, describes its regulative, semiotic, cultural and cognitive aspects. The phenomenon of cultural codes is studied from the perspective of a linguistic approach, which is based on the idea of their imagery nature. The author describes an imagery code as a system of images that are part of an ethnoculture, are established in the practice of communication, are normative in nature and serve as signs of fragments of reality. It is emphasized that the basis of the images is the so-called cultural realia. Under the cultural realia in this work the author understands different objects of the real world directly related to a certain culture and somehow involved in any kind of human activity. It is noted that physical objects, gaining meaning in the mind of a person, become signs. Objects related to a particular area of reality, in the process of semiosis form cultural codes. The article analyzes a number of imagery codes of culture, describing them as codes of cognition and communication. In addition, the author studies the function of a cultural code, substantiating the fact that any sphere of reality perceived by the sensory organs can fulfill the function of a cultural code.